PEMBERDAYAAN AISYIYAH CABANG KOWANGAN DALAM PEMANFAATAN RICEBRAN SEBAGAI PRODUK PANGAN FUNGSIONAL - Sufiati Bintanah; Mufnaety -; Abdulrohman - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Ricebran is a by product of rice milling finely texture containing bioactive components of food that is Orizanol and Tocopherol are beneficial for health. Bran can be obtain as much as 10 percent of the rice mill. Data from the Ministry of Agriculture, in 2012 the national rice production is producing 54.74 million tons 5.47 tons Ricebran. The purpose is increased skill and knowledge for functional food. Research methods is Ricebran with potential raw materials were abundant amount can be use as a basic ingredient of functional food products industry. Food diversivication program launching by the Ministry of Agriculture pemeintah through various programs realizing by the processing and marketing of agricultural products starting with the fortification of foodstuffs, food industry development of basic materials such as functional food ricebran so relating with food consumption patterns of safe, high quality and nutritionally balanced. Activities undertaken in this research is give training both in theory and practice and mentoring in the manufacturing, packaging and marketing of products. Results of this research, through the transfer of knowledge, technology and good management, Ricebran can be improved with the emergence processed into processed foods have high nutritional quality score and a high selling value and this is a business opportunity to raise additional revenue for group members The AisyiyahKeywords: Empowerment, Aisyiyah, Ricebran, Functional Food